Open data assessment in Italian and Spanish cities. - Sisto, Raffaele; García López, Javier; Paéz, José Manuel; Múgica, Elena Maté (Springer, 2018)
Citizens' attention to Open Data initiatives and Open Government policies is growing rapidly, but fragmentation in their implementation makes for a confusing approach. This research aims to bring structure to their assessment by analyzing 63 selected Spanish cities and 110 selected Italian cities and mapping their content. The analysis shows that (i) Open Data portals are not developed consistently; (ii) the various levels of public administration are not coordinated in their Open Data strategies; (iii) however, there are some good practices to be followed and underlined. Research into Open Data initiatives could benefit from previous examples regarding the success and failure factors of an Open Government. This paper highlights the main trends for an Open Data portal strategy in Spanish and Italian cities from the citizens' point of view. The basic content, structure of the websites, quality, accessibility, crosscutting nature and data visualization of the datasets have been assessed from the user's perspective. Currently, Spain has 115 open-data portals embedded in datos.gov.es (Government of Spain 2016), and Italy has 40 open-data portals at the city level. Open Data initiatives are the basis to achieve transparency, participation and collaboration, and also to establish the pillars for the integration of intelligent policies.
Keywords: Öffentliche Verwaltung; Transparenz; Open Data; Bürgerbeteiligung